Contribution to the study of glyceraldehyde-3-phosphate dehydrogenase in patients with type 2 diabetes - Senhaji, N; Elkhalfi, B; Soukri, A (Pathologie biologie (Paris), 2015)
Diabetes is recognized as a major public health problem responsible for early morbidity and mortality with a worldwide prevalence in permanent increase. The type II diabetes once called non-insulin dependent diabetes, accounts for about 90 % of all forms of diabetes and is characterized by abnormalities that affect insulin secretion and insulin action and thus, induces hyperglycemia. The aim of this work is to study the involvement of a key enzyme of glycolysis, glyceraldehyde-3-phosphate dehydrogenase in type 2 diabetes. This work includes a biochemical, kinetic studies, and the study of the expression of GAPDH in subjects with type 2 diabetes. From our study, we could classify the diabetic subjects into two categories: the first one, consisting of subjects in whom GAPDH has a specific activity and an electrophoretic profile similar to healthy subjects, and the second one, in which there is an inhibition of GAPDH. Our results suggest that, in 60 % of our patients with type 2 diabetes, a reversible inhibition of GAPDH is observed. This inhibition is probably mediated by the ionic interaction with the erythrocyte membrane protein, band 3.